In Vivo Degradation of Cholesterol to Bile Acids Is Reduced in Patients Receiving Parenteral Nutrition. (February 2014) - Carulli, Lucia; Del Puppo, Marina; Anzivino, Claudia; Zambianchi, Lisa; Gabbi, Chiara; Baldelli, Enrica; Odoardi, Maria Rosaria; Loria, Paola; Carulli, Nicola; Bertolotti, Marco
Background . Artificial nutrition is frequently associated with hepatobiliary complications, probably due to the inherent derangement of the gastrointestinal tract physiology. Alterations of hepatic lipid metabolism are likely to be involved. The aim of the present study was to investigate the effect of artificial nutrition on bile acid production, a key event in cholesterol homeostasis, in humans. Patients and Methods . Eleven patients receiving artificial nutrition, either parenteral nutrition (PN; n = 6) or enteral nutrition (EN; n = 5) with no previous history of liver disease, underwent analysis of cholesterol 7α-hydroxylation rates in vivo, a measure of bile acid formation, by isotope release analysis after intravenous injection of [7α- 3 H]cholesterol. The results were compared with those obtained in a population of 16 age-matched control subjects. Results . Hydroxylation rates were lower in patients with artificial nutrition (PN: 94 ± 13 mg/d; EN: 230 ± 39 mg/d, mean ± SEM) when compared with controls (385 ± 47 mg/d) ( P < .01, 1-way analysis of variance). In a patient receiving EN, hydroxylation rates increased 3.5-fold after treatment with the cholecystokinin analogue ceruletide (20 µg bid for 2 weeks intramuscularly). Serum lathosterol-to-cholesterol ratio, a marker of cholesterol synthesis, was also significantly reduced in artificial nutrition, whereas serum levels of fibroblast growth factor 19 (FGF19) were increased. Conclusion . In vivo 7α-hydroxylation is suppressed in artificial nutrition, particularly in PN. The finding associates with reduced cholesterol production, possibly as a metabolic consequence. The data suggest a regulatory role of gastrointestinal hormones and FGF19 on bile acid production and might suggest a pathophysiological basis for some common complications of artificial nutrition, such as gallstone disease and cholestasis.